2010
DOI: 10.1159/000323977
|View full text |Cite
|
Sign up to set email alerts
|

Downregulative Effects of Nitric Oxide on Oocyte Fertilization and Embryo Development: Possible Roles of Nitric Oxide in the Pathogenesis of Endometriosis-associated Infertility

Abstract: Aims: To investigate the effects of elevated nitric oxide (NO) levels in peritoneal fluids (PF) on oocyte fertilization and pre-implantation embryo development, and the relation of those effects to endometriosis-associated infertility. Methods: PF from women undergoing laparoscopy for infertility of minor endometriosis, tubal blockage and operation for tubal ligation was aspired at the pouch of the cul-de-sac during surgery. Oocytes and embryos of adult ICR mice were cultured in vitro with or without endometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In a previous study, 10 % or 30 % peritoneal fluid from minimal to mild endometriosis patients decreased the cleavage rate of 2-cell mouse embryos [24]. In the previous report, the effect of 10 % and 30 % peritoneal fluid is similar to the effect of 0.1~10 μM and 1 mM SNP concentration, respectively [24]. Therefore, the concentration of 10 μM SNP used in the present study was able to reflect the microenvironment effect of NO in the patients with endometriosis.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In a previous study, 10 % or 30 % peritoneal fluid from minimal to mild endometriosis patients decreased the cleavage rate of 2-cell mouse embryos [24]. In the previous report, the effect of 10 % and 30 % peritoneal fluid is similar to the effect of 0.1~10 μM and 1 mM SNP concentration, respectively [24]. Therefore, the concentration of 10 μM SNP used in the present study was able to reflect the microenvironment effect of NO in the patients with endometriosis.…”
Section: Discussionmentioning
confidence: 76%
“…In previous studies, excess oxidation and high levels of NO within endometrial tissue, follicular fluid, and peritoneal fluid were identified in patients with endometriosis [22,24,41]. Furthermore, studies of single nucleotide polymorphism s reveal that GSTT1 (glutathione-S-transferase) null deletion [36] and eNOS [20] are associated with moderate risk of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of NO in regulation of fertilization has also been studied in mammals but results are not consistent with the present findings in catfish. Luo et al (2010) have shown, however, that SNP decreases the fertilization rate in humans. Yang et al (2005) have observed an elevated rate of fertilization in vitro in comparison to the wild type fertilization, when either iNOS-deficient sperm or oocytes were used.…”
Section: Discussionmentioning
confidence: 97%
“…The ambiguous NO necessity could be a result of a more diverse NO effect when NO is associated with inflammation and/or oxidative stress [47, 48]. Accordingly, the role of NO during subsequent embryonic development after fertilization remains controversial [4951] for inflammation (endometriosis), accompanying NO [52, 53] and protein nitration [54]. However, creation of secondary products of NO interactions seems to be one of possible mechanisms of NO negative action [55].…”
Section: Gasotransmission In Female Reproductive Processesmentioning
confidence: 99%